2016
DOI: 10.1177/1060028016628893
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Randomized Controlled Trials Comparing Hypertonic Sodium Solutions and Mannitol for Traumatic Brain Injury

Abstract: Based on limited data, clinically important differences in mortality, neurological outcomes, and ICP reduction were not observed between HTS or mannitol in the management of severe TBI. HTS appears to lead to fewer ICP treatment failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 42 publications
0
44
0
3
Order By: Relevance
“…Clinical use of HTS has been introduced for prehospital intravascular volume restoration in patients with severe haemorrhage and is increasingly used for the treatment of brain oedema and h-ICP [9,10]. Recent guidelines suggest the use of HTS as a second-line therapy in cases where mannitol fails to reduce ICP [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical use of HTS has been introduced for prehospital intravascular volume restoration in patients with severe haemorrhage and is increasingly used for the treatment of brain oedema and h-ICP [9,10]. Recent guidelines suggest the use of HTS as a second-line therapy in cases where mannitol fails to reduce ICP [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent guidelines suggest the use of HTS as a second-line therapy in cases where mannitol fails to reduce ICP [8]. Despite hyperosmolar solutions being routinely used in neurosurgical and neurocritical care (NCC) patients for brain relaxation and ICP management [8][9][10][11][12][13][14], there is scanty information on the time course of their haemodynamic effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, these meta-analyses are limited, as there are several differences noted between studies (dosage used, when neurological and mortality outcomes were assessed, HSS formulas, unblinded trials, etc.). Furthermore, a randomized controlled trial with sufficient power is needed to make definite conclusions about the use and effectiveness of each drug [10,11]. Another method of ICP reduction is decompressive craniectomy, where a portion of the skull is removed to expand the area around the swelling brain [12].…”
Section: Traumatic Brain Injury: Definition Prognosis and Current Trmentioning
confidence: 99%
“…This systematic review wrote that the data which were currently used were still limited due to the high heterogeneity of each study. 34 A review by Boone et al, also found that because of the heterogeneity among studies, the superiority between hypertonic saline and mannitol in reducing ICP in patients TBI could ORIGINAL ARTICLE not be concluded. 35 Studies regarding comparison of effectivity of mannitol and hypertonic saline in lowering intracranial pressure for TBI patient were summarized in Table 1.…”
mentioning
confidence: 99%
“…34 This review involved seven well-publicized trials until November 2015. The failure rate of ICP-lowering therapy was less found in the hypertonic saline group.…”
mentioning
confidence: 99%